Numerical Characteristics on the Set of Heteroclinic Points of Morse–Smale Diffeomorphisms on Surfaces - Vlasenko, I. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For Morse–Smale diffeomorphisms on closed surfaces, we investigate the properties of numerical characteristics of heteroclinic trajectories with respect to the local structure of direct product in a small neighborhood of a saddle periodic point.